Two Days' Diggings in Sutherland (Proceedings of the Society of Antiquaries of Scotland, 1865)
An account of the excavation of a broch near Brora. Animal remains were discovered during the excavation of the broch, and a cist, human remains and a sculptured stone that were found nearby. The author also investigated an underground chamber and some barrows in the area.